2011
DOI: 10.1002/jsfa.4604
|View full text |Cite
|
Sign up to set email alerts
|

Composition of hydroponic lettuce: effect of time of day, plant size, and season

Abstract: The greatest yield on a fresh weight basis was obtained by harvesting lettuce at dawn. Although dry matter or sugar content increased later in the day, there is no commercial benefit to delaying harvest as consumers do not buy lettuce for these attributes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…According to Lin et al (2013), nitrate content in lettuce leaves was significantly affected by light quality, while Petropoulos, Chatzieustratiou, et al (2016) have reported the effect of harvest time, growing period and nitrogen fertilization rates on nitrates content of parsley leaves. Moreover, Gent (2012) has reported that nitrate content in leafy vegetables is inversely related with organic acids and sugar content, which was also the case in our study and especially for the 3rd growth stage where nitrate content decrease was followed by an increase in organic acids and sucrose content.…”
Section: Tablesupporting
confidence: 88%
“…According to Lin et al (2013), nitrate content in lettuce leaves was significantly affected by light quality, while Petropoulos, Chatzieustratiou, et al (2016) have reported the effect of harvest time, growing period and nitrogen fertilization rates on nitrates content of parsley leaves. Moreover, Gent (2012) has reported that nitrate content in leafy vegetables is inversely related with organic acids and sugar content, which was also the case in our study and especially for the 3rd growth stage where nitrate content decrease was followed by an increase in organic acids and sucrose content.…”
Section: Tablesupporting
confidence: 88%
“…In spring, the differences in the leaf water content were maintained with the delay to processing, while in winter the differences among harvests were homogenized with the delay to processing. Environmental factors have been described to influence the dry matter content of lettuce (Gent, 2012). Clarkson et al (2005) reported in salad roquette and red chard that higher turgor pressure was shown at end-of-day harvest (22:00 h) and this contributed to a more processable leaf with extended postharvest shelf life.…”
Section: Seasonmentioning
confidence: 99%
“…Thus, several heat shock proteins, nitrate and ascorbic acid concentrations varied significantly over the 24 h period (Li et al, 2000;Gent, 2012;Chang et al, 2013). Ascorbic acid decreased to the lowest level around 6 h after the light intensity initially increased (Chang et al, 2013) while nitrate increased during a dark period but decreased in light (Gent et al, 2012;Chang et al, 2013). Hence, to reduce the nitrate content of spinach, leaves should be harvested after light levels initially increase (Chang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Berezin et al 3 , Conn et al 4 , and Alatorre-Cobos et al 2 used hydroponic systems and several plant species including tomato and tobacco, to generate sufficient plant biomass for mineral analysis [2][3][4] . Industrial applications of hydroponics have also been developed for crops such as tomato and lettuce 6 . Here, we outline the use of hydroponics in the context of research, possible variations in available methods, and finally present a system that can be easily scalable and useful for research laboratories interested in studying plant mineral nutrition.…”
Section: Introductionmentioning
confidence: 99%